What and How to Communicate CSR? The Role of CSR fit, Modality Interactivity, and Message Interactivity on Social Networking Sites. (3rd September 2017) - Go, Eun; Bortree, Denise Sevick
ABSTRACT: The current study explored how organizations can build credibility of their CSR communication in social media. In particular the study investigated the role of CSR fit, modality interactivity and message interactivity through a 2 × 2 × 3 experimental design ( N = 299). The results suggest that promoting CSR activities with a good fit for the organization leads to greater credibility. Message interactivity also leads to greater credibility perception by way of imbuing a sense of social presence and openness to communication; however, modality interactivity did not significantly influence credibility. Additional analysis suggests an interaction between CSR fit and message interactivity that makes fit critical in low-interactivity settings. Implications for public relations research and practice are discussed.